X-ray crystallographic analysis of cytochrome c' from two bacterial species : this thesis is submitted as partial fulfilment of the requirements for the degree of Doctor of Philosophy in Chemistry at Massey University - Dobbs, Aaron John; Dobbs, Aaron John (Massey University, 1995)
The structure of cytochrome c' from two closely related bacterial species, Alcaligenes sp and Alcaligenes denitrificans, have been determined from X-ray diffraction data to 1.80 Å and 2.15 Å resolution respectively using the anomalous scattering of the single iron atom in each to identify and refine a weak molecular replacement solution. Molecular replacement studies, with the program AMORE, used two isomorphous data sets (from the two species), two independent search models (the cytochromes c' from Rhodospirillum molischianum and Rhodospirillum rubrum), both with and without sidechains, and two different resolution ranges (10.0-4.0 Å and 15.0-3.5 Å) to generate a large number of potential solutions. No single solution stood out and none appeared consistently. The iron position in each structure was then determined from its anomalous scattering contribution and all molecular replacement solutions were discarded which did not (i) place the iron correctly and (ii) orient the molecule such that a crystallographic 2-fold axis generated a dimer like those of the two search models. Finally, electron density maps phased solely by the iron anomalous scattering were calculated. As these were combined and subjected to solvent flattening and histogram matching (program SQUASH), correlation with the remaining molecular replacement solutions identified one as correct and enabled it to be improved and subjected to preliminary refinement. The correctness of the solution was confirmed by parallel isomorphous replacement studies. Both crystal structures have been refined using least-squares methods, to give final R-factors of 0.184 for the Alcaligenes sp cytochrome c' (953 protein atoms and 89 solvent molecules) and 0.167 for the Alcaligenes denitrificans cytochrome c' (950 protein atoms and 75 solvent molecules). Analysis and comparisons of these structures with three cytochrome c' structures previously determined show that despite the low level of sequence conservation among the family members the gross overall structure is maintained (four-α-helix bundle). The configuration of the iron ligands and of the surrounding haem environment are very similar indicating that although residues are not conserved they are replaced by residues which fulfil a similar function. There are relatively few sidechain...sidechain interactions in cytochromes c' which probably reflects the fact that the majority of stabilising i interactions are hydrophobic in nature. This hydrophobic packing could also explain the lack of sequence identity between the different species of cytochrome c' as strict conservation of the residues is not required. All the structures do have a similar haem stabilisation framework, with an approximately ten residue piece of structure situated in the BC loop involved in both haem stabilisation and interhelix stabilisation in all of the cytochromes c' determined. The overall four-helix structure is also discussed in terms of its parameters with respect to the current interest in the de novo design of proteins.
Keywords: Alcaligenes; Haemproteins; Hemeproteins